Application of a Rapid ESI-MS/MS Method for Quantitative Analysis of ocetaxel in Mouse Biological Matrices Through Direct Injection to Mass Spectrometer - Rafiei, Pedram; Alcorn, Jane; Haddadi, Azita (Current Pharmaceutical Analysis, 2018)
Background: Docetaxel is a potent anticancer agent used in various cancer types. Attempts are being made to improve docetaxel's pharmacokinetics because desirable modifications in disposition and biodistribution characteristics could enhance the therapeutic outcomes of the drug. Quantitative analysis of docetaxel in the body is important to understand modifications necessary to improve the drug's biodistribution and pharmacokinetics. Majority of studies have applied HPLC coupled with mass spectrometry (LC-MS) or HPLC alone to quantitatively analyse docetaxel in various matrices. Long separation times, many resources, and additional techniques are usually required to establish a proper liquid chromatographic (LC) method. Objective: Development and validation of a simple and rapid mass spectrometric method (ESIMS/ MS) for quantification of docetaxel in mouse biological matrices were the objective of the study. Methods: Docetaxel was extracted from mouse serum and liver using a liquid-liquid extraction with tert-butyl methyl ether. Samples were direct-injected to the instrument using 0.1% formic acid in methanol as the mobile phase (isocratic elution). Method development and validation were performed according to FDA guidelines. Detection was done by a Hybrid Triple Quadrupole/Linear Ion trap instrument through positive ESI source and MRM mode. Result: Docetaxel retention-time was about 0.6 min while the total run-time was 2 min. The method was linear, sensitive, and specific with an acceptable level of precision and accuracy and was successfully applied for rapid quantitative analysis of docetaxel in mouse biological matrices. Conclusion: The validated method allows simple and fast analysis of docetaxel in biological samples for pharmacokinetic and biodistribution studies.
Keywords: Multiple reaction monitoring (MRM)